LA PROGRAMACIÓN LIMPIA, MODULADA Y ORIENTADA A POSICIONAMIENTO EN EL DESARROLLO DE APLICACIONES ORIENTADAS A INTERNET EN LA UNIVERSIDAD TÉCNICA DE BABAHOYO. - Guaman Sanchez, Julio Cesar (2018)
This research work aims to explain what is related to the use of clean programming, modulated and oriented to positioning in the development of internet-oriented applications through a document that collects all perspectives from various points of view towards an approach in which the developer must possess the necessary knowledge for the adoption and coupling of new techniques that allow him to develop applications with socio-dependent characteristics that help to obtain the desired level of positioning in the Technical University of Babahoyo (UTB); For this, a digital ecosystem is sketched in which all the necessary elements for the technical deployment and positioning in the development converge with the use of the Vista Controller Model as the ideal technique to achieve the proposed objective. The research is direct observation and descriptive type field, the sample was taken in a population of 100 people between men and women (students, graduates and professionals) which are developed in the area of ​​software development, In relation to the data collection instrument, we chose the surveys constructed by 10 questions with several alternative answers, concluding with several points of view in which the impact and the best route for the positioning of the development of applications oriented to Internet.